2007
DOI: 10.1002/cncr.22453
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, dietary, and lifestyle factors in the prevention of colorectal adenomas

Abstract: BACKGROUND.Many studies have suggested a role for calcium in reducing the risk of colorectal adenomas and cancer but its effectiveness may be dependent on interactions with other dietary and/or lifestyle factors. We examined the association between calcium and prevalence of adenomas and assessed whether the association was stronger in biologically plausible subgroups.METHODS.Cross‐sectional data from 222 cases and 479 adenoma‐free controls who underwent colonoscopies and completed food frequency and lifestyle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…A total of 14 studies 11,[14][15][16][27][28][29][30][31][32][33][34][35][36] were eligible for the inclusion in dose-response meta-analysis of total calcium intake and adenoma risk (Supporting Information Table 2). Across the studies, types of adenomas investigated varied.…”
Section: Total Calcium Intakementioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 studies 11,[14][15][16][27][28][29][30][31][32][33][34][35][36] were eligible for the inclusion in dose-response meta-analysis of total calcium intake and adenoma risk (Supporting Information Table 2). Across the studies, types of adenomas investigated varied.…”
Section: Total Calcium Intakementioning
confidence: 99%
“…While accumulating evidence suggests that calcium may be more protective against advanced adenomas, 9,11,16,29,35 there is no sufficient a priori evidence to suspect that the effect of calcium may differ by recurrent versus occurrent adenomas. Thus, doseresponse meta-analysis of total calcium intake and adenoma risk was based on 13 studies 11,[14][15][16][28][29][30][31][32][33][34][35][36] excluding the study by Lieberman et al, 27 which was included only in the subgroup analysis for high-risk adenomas.…”
Section: Total Calcium Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies that examined the relationship between circulating 25(OH)D and colorectal adenomas were identified, including four case-control studies (15,29,31,32), one nested case-control study (33), two cohort studies (14,26), and one cross-sectional study (34). Seven of the eight studies identified were included in this analysis ( (29).…”
Section: Circulating 25(oh)dmentioning
confidence: 99%
“…Seven of the eight studies identified were included in this analysis ( (29). Six studies accounted for season of blood draw: one study matched controls by date of blood draw (33), and five studies (14,15,26,31,34) adjusted for month of blood draw. One study did not adjust for seasonality (29).…”
Section: Circulating 25(oh)dmentioning
confidence: 99%